Biofilm Technology in the Production of Macrobrachium rosenbergii: an Appraisal of Feasibility - a Short Review - Sow, Cyn Shieng; Md Yusoff, Fatimah; Mohamed Ramli, Norulhuda; Lim, Keng Chin; Abd Karim, Murni Marlina (Malaysian Journal of Science, 2024)
This review examines biofilm formation, composition, and its impact on prawn culture. It investigates the factors that influence the development of biofilms and their interactions with the giant freshwater prawn, Macrobrachium rosenbergii within the context of nutrient-rich biofilms. This review also explores the concept of biofilm production and its application in giant freshwater prawn cultivation, including the incorporation of probiotics. This study investigates the effects of biofilms on vital water quality parameters, including pH, ammonia level, and dissolved oxygen. It also examines the effects on the health and growth of crustaceans. Aquaculture's rapid growth has impacted the environment in several countries. The M. rosenbergii prawn holds significant importance as an aquaculture species in Malaysia, demonstrating the ability to enhance the income of farmers experiencing economic difficulties. However, large amounts of water are used, high-nutrient effluents are released, large areas are occupied, natural habitats are changed, and exotic species escape from their habitats. Several studies have demonstrated the application of biofilm technology in enhancing the production, safety, and economic sustainability of M. rosenbergii farmers. Biofilms are microbial consortiums embedded in extracellular polymeric substances (EPS) that adhere to submerged surfaces. This microbial cell consortium reduces ammonium and phosphate concentrations in aquaculture systems, providing a food source for the cultured species. Many studies have focused on the alternative microbial species with promising results. Therefore, the benefits of biofilm technology in the production of M. rosenbergii are reviewed to facilitate future research, development, and applications in aquaculture.